2023
DOI: 10.1002/dad2.12425
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructural metrics are sensitively associated with clinical staging in Alzheimer's disease

Abstract: Introduction White matter microstructure may be abnormal along the Alzheimer's disease (AD) continuum. Methods Diffusion magnetic resonance imaging (dMRI) data from the Alzheimer's Disease Neuroimaging Initiative (ADNI, n = 627), Baltimore Longitudinal Study of Aging (BLSA, n = 684), and Vanderbilt Memory & Aging Project (VMAP, n = 296) cohorts were free‐water (FW) corrected and conventional, and FW‐corrected microstructural metrics were quantified within 48 white matter tracts. Microstructural values were sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
(101 reference statements)
1
4
0
Order By: Relevance
“…61-63 In previous work, we have shown that the FW measure, particularly in limbic tracts, is sensitive to abnormal aging. 28,49 This study extends this work by showing that APOE -ε4 carriers, who are known to be at greater risk for AD, show these same changes in the FW metric in limbic tracts. This suggests that processes that increase interstitial spaces, such as atrophy, inflammation, or edema, are present to a greater extent in APOE -ε4 carriers in tracts known to be affected in AD.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…61-63 In previous work, we have shown that the FW measure, particularly in limbic tracts, is sensitive to abnormal aging. 28,49 This study extends this work by showing that APOE -ε4 carriers, who are known to be at greater risk for AD, show these same changes in the FW metric in limbic tracts. This suggests that processes that increase interstitial spaces, such as atrophy, inflammation, or edema, are present to a greater extent in APOE -ε4 carriers in tracts known to be affected in AD.…”
Section: Discussionsupporting
confidence: 74%
“…28,53 While some studies have shown that projection fibers are also associated with abnormal cognitive aging, these associations are less robust. 10,28,49 Given that females are disproportionately affected by AD, the observed sex differences in FA FWcorr in our study suggest that white matter integrity may contribute to this disparity. However, we also found that in tracts with sex differences in FW, females tended to have lower values than males longitudinally.…”
Section: Discussionmentioning
confidence: 64%
“…The cingulum bundle is critical for cognitive and emotional processing, and disruption of its microstructure can lead to impaired connectivity between the frontal lobe and other brain regions, contributing to the cognitive decline in AD patients. 67,68 The corpus callosum (CC), the largest white matter structure in the brain, facilitates inter-hemispheric communication. The impact on the corpus callosum (including forces major, forceps minor, and the middle sector of CC) is of great interest, as it plays a crucial role in coordinating cognitive and motor functions across the two brain hemispheres.…”
Section: Discussionmentioning
confidence: 99%
“…We use (i) the mean FA values for 112 of the 118 regions of the EVE Type-III atlas for each participant; (ii) covariates of age, sex, cognitive status, race, education, APOE2 carrier status, and APOE4 carrier status, the covariates used in DTI harmonization by Yang et al; 36 and (iii) a covariate indicating the dataset the participant scan came from. Six regions are excluded from consideration because the registration process resulted in regions with zero volume, which could induce a large shift in the mean of the distribution of mean FA values for the cohort.…”
Section: Combat Harmonizationmentioning
confidence: 99%